Hydrogen Production from catalytic acetic acid steam reforming over bimetallic Ni-Co on La2O3 Catalyst- Effect of Catalyst dilution - Tuan Abdullah, Tuan Amran (2013)
Catalytic steam reforming of acetic acid using bimetallic catalysts of 5 wt.% nickel and 5 wt.% cobalt supported on Lanthanum (III) oxide (La2O3) for hydrogen production was investigated in a micro fixed bed reactor. The reactor was of quartz tube with a 10 mm inside diameter. The effect of catalyst dilution on the reaction was studied. Silicon carbide was used as the dilution material. The experiments were conducted at atmospheric pressure and temperatures ranging from 500 to 700°C. The complete conversion of acetic acid to product gases has been observed at 550°C and 700°C for diluted and non-diluted catalysts respectively. It shows that catalyst dilution had a profound effect on the conversion of acetic acid at low temperature (550°C) whilst high temperature of 700°C was required for the non-diluted catalyst. The product gas distributions are similar when using both diluted and non-diluted catalysts.